Soil erosion rates based on anatomical changes in exposed roots - case study from southwest Bulgaria - Pavlova-Traykova, Eli; Dimitrov, Dimitar (Silva Balcanica (Sofia), 2023)
In recent years different methods for soil erosion assessment have been used. Because of its high accuracy in estimations, dendrogeomorphology was selected as one suitable and reliable scientific method to achieve the main goals of this study. The main goal of the study is to date denudation events using anatomical responses of the tree-rings of the roots. We analyze the histological changes that occur in the roots of two tree species, along the river banks of the Sedelska River, which is a tributary of Struma River. The significant differences between homogenous groups of measurements in pre-exposed and exposed roots was established, and it shows a remarkable response of roots to sheet erosion.